Des flots à contre-courant : des montagnes du Lesotho à la métropole sud-africaine - Yannick Rousselot (Revue de Géographie Alpine)
The aim of this article is to consider the mountains of Lesotho as suppliers of water to the Gauteng metropolitan area in South Africa. By analysing the hydropolitics of the Southern African region in the context of politics of scale, the focus is on the Lesotho Highlands Water Project (LHWP), a transboundary water transfer project between Lesotho and South Africa. The goal is to link hydropolitics with territorialities. The LHWP has resulted in a reproduction of the asymmetrical relations between and inside the metropolitan and mountain areas of both countries. Coalitions of actors have emerged from these new relations that the transfer has produced, and as such, this project should be analysed as a hydraulic assemblage in which three distinct scales of territorialities are clashing or cooperating with each other: the regional scale, made up of South Africa’s political and economic elites, who seek to direct Southern Africa’s water resources towards the thirsty region in and around Johannesburg; the scale of the Lesotho government, which has a nationalist policy of monopolising any social and spatial stakes for the benefit of the national territory; and the scale of the Maloti communities, which claim their rights as a transnational Basotho nation and autonomy in the face of interventionism from the Lesotho state.